Integrating Benevolence in the Islamic Digital Canvas Marketing Model for Promoting Sharia-Compliant P2P Lending Platforms: A Comprehensive Approach - Romi Setiawan (Journal of Nusantara Economy, 2023)
The purpose of this study is to introduce the Islamic Digital Marketing Canvas Model to market Sharia-compliant Peer-to-Peer (P2P) lending platforms. This model attributes to the digital channels and platforms to strategically engage the Islamic finance audience by incorporating the sharia principles. There are five key components introduced which are value proposition, goals and objectives, content strategy, channels, measurement, and optimization. This model offers a structured approach for designing, implementing, and evaluating marketing strategies within the context of P2P lending platforms. The study employs a qualitative research method supplemented by a literature review approach. Drawing upon modern digital marketing practices and principles of Islamic finance, this study introduces benevolence (ihsan) as a novel element within the Islamic Digital Marketing Canvas model, offering a comprehensive and flexible framework for enhancing sharia awareness, engagement, and growth in Sharia-compliant P2P lending platforms. This study contributes to the evolving field of Islamic fintech marketing by presenting a strategic approach that aligns digital marketing tactics with Sharia values and financial innovation.